HUBUNGAN IMPLEMENTASI CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN HASIL BELAJAR SISWA MATA PELAJARAN KIMIA DI KELAS X MIA SMA NEGERI 8 KOTA BENGKULU - Pebri Tri Andiko; Salastri Rohiat; Elvinawati Elvinawati (ALOTROP, 2019)
This study aims to analyze the relationship of Contextual Teaching and Learning (CTL) implementation with students' learning outcomes in X class MIA SMA Negeri 8 Kota Bengkulu at 2017/2018 Academic year. This type of research is correlational research. The population in this research is class X MIA SMA Negeri 8 Kota Bengkulu 2017/2018 Academic year and research using total sampling technique where all population used also become sample of research with total 166 students. Data collection techniques in this study using questionnaires, observation sheets and students' chemistry learning results. Data analysis using Pearson correlational analysis and validation test, reliability, normality, linearity (with F test) , and hypothesis test. Based on the results of data analysis that has been done, obtained general conclusion of a positive relationship between the application of Contextual Teaching and Learning (CTL) with the results of students learningoutcomes in X class MIA SMA Negeri 8 Kota Bengkulu at 2017/2018 Academic year, indicated by the value rhitung obtained greater than the value of tabell r (0.704> 0.1281) with the level of correlation into the category of strong / high, it means there is a positive and strong relationship between the application of Contextual Teaching and Learning with student learning outcomesin X class MIA SMA Negeri 8 Kota Bengkulu at 2017/2018 Academic year.